2005
DOI: 10.1289/ehp.8043
|View full text |Cite
|
Sign up to set email alerts
|

Workgroup Report: Drinking-Water Nitrate and Health—Recent Findings and Research Needs

Abstract: Human alteration of the nitrogen cycle has resulted in steadily accumulating nitrate in our water resources. The U.S. maximum contaminant level and World Health Organization guidelines for nitrate in drinking water were promulgated to protect infants from developing methemoglobinemia, an acute condition. Some scientists have recently suggested that the regulatory limit for nitrate is overly conservative; however, they have not thoroughly considered chronic health outcomes. In August 2004, a symposium on drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
422
1
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 683 publications
(474 citation statements)
references
References 88 publications
3
422
1
11
Order By: Relevance
“…Estimates of dietary nitrate and nitrite intake may also be useful. And, finally, for studies in which nitroso compound exposure is of particular interest, collection of a variety of other measures, such as measures of endogenous exposure to these compounds in saliva, urine or feces; biomarkers of genotoxicity; CYP2E1 genotype; and dietary intake of nitrosatable amines and amides, and vitamin C and other nitrosation inhibitors may be useful or necessary (Ward et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of dietary nitrate and nitrite intake may also be useful. And, finally, for studies in which nitroso compound exposure is of particular interest, collection of a variety of other measures, such as measures of endogenous exposure to these compounds in saliva, urine or feces; biomarkers of genotoxicity; CYP2E1 genotype; and dietary intake of nitrosatable amines and amides, and vitamin C and other nitrosation inhibitors may be useful or necessary (Ward et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the problem occurs very quickly and often the cattle are observed to be normal one day and dead the next day [8]. Ward et al [9] reviewed the epidemiologic evidence for the linkages between drinking water 3 …”
Section: Nomentioning
confidence: 99%
“…Most cases of methemoglobinemia were reported in the 1940s where methemoglobinemia or "baby blue syndrome" was seen in infants fed formula with nitrate contaminated well-water (Powlson et al, 2008). It was later suggested that methemoglobinemia was not caused by nitrate but by fecal bacteria contamination in the well-water or bacterial nitrate reduction in vivo that may have caused the intestinal infection, and this may have been responsible for the nitrate-induced methemoglobinemia in the infants (Hanukoglu & Danon, 1996;Ward et al, 2005). Of interest, nitrate was used in very high doses (often for weeks) at the beginning of the last century as a diuretic (Butler & Feelisch, 2008).…”
Section: Potential Toxicity Of Nitrite and Nitratementioning
confidence: 99%